2018
DOI: 10.1007/s00411-018-0740-y
|View full text |Cite
|
Sign up to set email alerts
|

FT-IR investigations on effect of high doses of gamma radiation-induced damage to polystyrene and mechanism of formation of radiolysis products

Abstract: The present article focuses on the influence of gamma irradiation and post-irradiation storage conditions on FT-IR spectra of 1 mm thick polystyrene irradiated with 51, 77 and 129 kGy. The increase in amplitude corresponding to 3600, 3400 and 2100 cm stretching frequencies clearly showing the formation of O-H and C=O bonds (~ 25%). On prolonged storage (2160 h) in the dark, there is an increase in O-H group (~ 28%). The electron cloud facilitates the formation of hydroxyl group in irradiated polystyrene. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
1
6
1
Order By: Relevance
“…No peaks are missing and no peak shifts were observed, confirming that the iPP retains its crystal structure even after gamma-ray or e-beam irradiation [ 29 , 30 ]. Although some studies showed [ 31 , 32 ] that gamma-ray irradiation forms hydroxyl (OH) and carbonyl (C=O) groups on polymers such as iPP, we did not observe any peaks corresponding to these groups at any dose [ 33 ].
Fig.
…”
Section: Resultscontrasting
confidence: 81%
“…No peaks are missing and no peak shifts were observed, confirming that the iPP retains its crystal structure even after gamma-ray or e-beam irradiation [ 29 , 30 ]. Although some studies showed [ 31 , 32 ] that gamma-ray irradiation forms hydroxyl (OH) and carbonyl (C=O) groups on polymers such as iPP, we did not observe any peaks corresponding to these groups at any dose [ 33 ].
Fig.
…”
Section: Resultscontrasting
confidence: 81%
“…In addition, no chemical changes were observed in Raman analysis of gamma-irradiated facemasks up to 25 kGy. Although few studies show that >50 kGy gamma irradiation forms carbonyl and hydroxyl groups in iPP fiber, 70 however, in the present study, corresponding peaks were not present, which is in line with other work. 21
Figure 2.Raman spectra of pristine and sterilized filter layer of the respirators.
…”
Section: Evaluation Of Physical Chemical and Morphological Properties...supporting
confidence: 92%
“…These indicate the presence of polystyrene (PS) in the waster toner. 34 In addition, the asymmetric stretching vibration and symmetrical deformation vibration of C-H in methyl groups appear at 2956 cm À1 and 1396 cm À1 , and C-H out-plane deformation vibration of terminal olefin is also observed at 906 cm À1 . 35 In addition, CQO strong stretching vibration at 1723 cm À1 , 10 and C-O asymmetric and symmetric stretching vibrations at 1261 cm À1 and 1157 cm À1 originate from ester groups.…”
Section: Njc Papermentioning
confidence: 98%